De-Islamophobia di Inggris melalui Sepak Bola: Kajian terhadap Mohamed Salah dan Liverpool - Wibowo, Bromo Yudo; Surwandono, Surwandono (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
This article aims to explain the role of Muslim professional sports actors in the activity of reducing prejudice against Islam in the UK, where in the last 10 years the trend of Islamophobia has increased sharply. This idea is important to see how the da'wah of Islam by using a soft power approach turns out to make a meaningful contribution to the development of Islamic da'wah today. This study uses a qualitative approach to understand the role of Muhammad Salah who is able to change the image of Islam in the UK, from a frightening image to a pleasant and entertaining image. Data was obtained from a number of secondary sources from social media metrics that developed in the UK. This article finds that the appearance of a professional Muslim sportsman who focuses on his field of expertise, is productive in the sense of being the best, and remains consistently a Muslim with good attitudes and behavior, is able to change the views of people outside Islam to find out more about Islam, and behave towards it in a professional and friendly manner.